O ensinamento sobre a justiça em Mateus: uma interpretação exegético teológica - Santos, Arthur Francisco Juliatti dos (2011)
The research has four chapters with an exegetical and theological study on the Greek word dikaiosu,nh (righteousness) in the Biblical context, as project, in the sermon of the mountain and as praxis, in the seven places where it appears (3:15; 5:6,10,20; 6:1,33; 21:32). Righteousness if you hunger or thirst (5:6), persecuted for righteousness sake (5:10) and it must surpass that of the scribes and the Pharisees (5:20). The imperative exhortations of 6:1,33 show that the intention guarantees rewards (6:1) and that priority, together with the kingdom is essential (6:33). Jesus must fulfil all righteousness (3:15), taking the path of the justice fully through which had come the prophets and, finally, John the Baptist (21:32). Jesus excludes the legal integralism and demands a perfection that is not ethical theatric, but a new way to act and to live, with the imperative exhortations of 6:1: beware (prose,cete) and 6:33 to you: seek (zhtei/te). The Kingdom and its justice have historical, social, economical and politics mediations in which the Christian is invited not to be anxious and but to free himself of the fear of losing security. The Hebrew Word hq"d"c. and the Greek dikaiosu,nh has passed semantic transformations that research seeks to define from a hermeneutic historical context, analysis semantics and philological and synoptic verification, in order to search its meaning in Matthew, where the word is used as a stylistic resource whose express moral rectitude and solidarity as to fulfill the will of the Father. The solidarity of Jesus in 3:15, had its starting point in the incarnation (the Word became sa,rx of Jo 1,14) and reached its fullness at the cross (the kh,nosij of Phi 2,6-11). Matthew touches the soil of human behaviour, insisting on the path of justice (21:32), as compendium of Jesus ethic´s as irreprehensible obedience to the Father, in an active solidarity that brings consequences for the life of the Church. The expression of this in Latin America is the preferential option for the poor persons, therefore God when intervening in history human being never made it in neutral ways, but always he was by the side of the weak and oppressed (cf. Ex 22:21-22; Deut 26:4ss; Isa 58:2ss). It is a mystic commitment that the Social Doctrine of the Church has and a constant search of solidarity with human nature and its history. The kingdom is not confused with the establishment of a just society, but it is not indifferent. The teaching about the righteousness in Matthew guides to the direction of fair act and just solidarity with God and for him, that is, behaviour that expresses a new orientation of the existence